2018
DOI: 10.1007/978-1-4939-7526-6_10
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Guide to Using the Endothelin-1 Model of Stroke in Conscious Rats for Acute and Long-Term Recovery Studies

Abstract: Multiple methods exist to model permanent and transient ischemia under anesthesia in animals, however most human strokes occur while conscious. The use of endothelin-1 as a vasoconstrictor applied to the perivascular surface of the middle cerebral artery is one of the only methods for inducing stroke in conscious animals. Here, we describe standard operating procedures for stereotaxic placement of an ET-1 guide probe above the middle cerebral artery, induction of stroke in conscious rats, predictive outcome sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…When exogenously supplemented in high concentrations at the MCA, severe vasoconstriction leads to occluded blood flow and infarcted brain tissue similar to that observed in the setting of human stroke. Abeysinghe and Roulston report in a detailed protocol [189] that the surgery begins by anesthetizing the subject and mounting it onto a stereotaxic frame. The scalp is then exposed, allowing for positioning of screws and an injector guide cannula (some protocols, comparable to that reported by Ansari and colleagues [190], additionally mount a laser Doppler probe to measure the drop in blood flow during the ET-1 injection).…”
Section: Endothelin-1 Induced Strokementioning
confidence: 99%
See 2 more Smart Citations
“…When exogenously supplemented in high concentrations at the MCA, severe vasoconstriction leads to occluded blood flow and infarcted brain tissue similar to that observed in the setting of human stroke. Abeysinghe and Roulston report in a detailed protocol [189] that the surgery begins by anesthetizing the subject and mounting it onto a stereotaxic frame. The scalp is then exposed, allowing for positioning of screws and an injector guide cannula (some protocols, comparable to that reported by Ansari and colleagues [190], additionally mount a laser Doppler probe to measure the drop in blood flow during the ET-1 injection).…”
Section: Endothelin-1 Induced Strokementioning
confidence: 99%
“…To induce the stroke in a freely moving animal, a microinjector is loaded with ET-1 solution, inserted into the guide cannula, and steadily released at the site of the MCA. Some behavioral measures to assess stroke outcome in the ET-1-induced stroke model include the neurological deficit score, sensorimotor hemineglect, rotarod motor performance, cylinder test, and staircase test [189].…”
Section: Endothelin-1 Induced Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Development of a stroke-induced animal model for preclinical tests and modalities to build such an animal model are being extensively investigated [16][17][18][19]. A typical stroke animal model investigation is achieved either through surgical blocking of specific vessels [20][21][22] or through a biochemical method [23,24]. However, stroke in local brain regions is investigated using photochemical thrombosis.…”
Section: Photochemical Thrombosis-based Stroke Animal Model Establish...mentioning
confidence: 99%
“…Up to 80% of silent brain infarcts have been demonstrated to be cortically located, especially in postsurgical, high vascular risk populations (Nah et al, 2014). Microinjection of the potent vasoconstrictor endothelin-1 has become a widely used approach to model focal ischemic injury in rodents with the capacity to modulate severity based on dosage (Abeysinghe & Roulston, 2018). We recently reported that ET-1 injection into the sensorimotor cortex of athymic rats that have a compromised immune system resulted in a focal ischemic injury associated with a stable motor impairment over 36 weeks (Ermine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%